If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5x + 13) + -2 = -6(3x + -2) + -41 Reorder the terms: -2(13 + 5x) + -2 = -6(3x + -2) + -41 (13 * -2 + 5x * -2) + -2 = -6(3x + -2) + -41 (-26 + -10x) + -2 = -6(3x + -2) + -41 Reorder the terms: -26 + -2 + -10x = -6(3x + -2) + -41 Combine like terms: -26 + -2 = -28 -28 + -10x = -6(3x + -2) + -41 Reorder the terms: -28 + -10x = -6(-2 + 3x) + -41 -28 + -10x = (-2 * -6 + 3x * -6) + -41 -28 + -10x = (12 + -18x) + -41 Reorder the terms: -28 + -10x = 12 + -41 + -18x Combine like terms: 12 + -41 = -29 -28 + -10x = -29 + -18x Solving -28 + -10x = -29 + -18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18x' to each side of the equation. -28 + -10x + 18x = -29 + -18x + 18x Combine like terms: -10x + 18x = 8x -28 + 8x = -29 + -18x + 18x Combine like terms: -18x + 18x = 0 -28 + 8x = -29 + 0 -28 + 8x = -29 Add '28' to each side of the equation. -28 + 28 + 8x = -29 + 28 Combine like terms: -28 + 28 = 0 0 + 8x = -29 + 28 8x = -29 + 28 Combine like terms: -29 + 28 = -1 8x = -1 Divide each side by '8'. x = -0.125 Simplifying x = -0.125
| 3[x-1]=49 | | 5(z+4)+1=7-(z+4) | | 12x^2-30x+48=0 | | A^2+15+54=0 | | -7=9+4c | | x-6y=50 | | t/-4-11 | | 2n/3=20/2 | | 58=4-9x | | 4s+8s= | | 5/(3x)^-4=? | | 5/(3x)^-4= | | 2Sin(X-10)=0.8 | | 2n/3=10/2 | | 5/(3x)^-4 | | 32x^2+76x-91=0 | | -4(6n-6)+4= | | .25x+.35y=5 | | x^2+4x-5=7 | | 2Sin(X-10o)=0.8 | | 8(x-5)=-20 | | -5n(7n-4)+4n= | | 32x^2-76x-91=0 | | A-15+a=a-15 | | 5a+1=7-a | | 5q+7=3(4-p) | | 2(x-5)-3=4x-2(5+x) | | 7x-6=6x+1 | | 3x+13=5x-27 | | z^3=13j | | -22+21=m-10 | | H=9x+4c-9+3x-8c+3 |